The Potential for cross-drive analysis using automated digital forensic timelines - Patterson, Jonathan; Hargreaves, Christopher J. (Cranfield University, 2012)
Cross-Drive Analysis (CDA) is a technique designed to allow an investigator to “simultaneously consider information from across a corpus of many data sources”. Existing approaches include multi-drive correlation using text searching, e.g. email addresses, message IDs, credit card numbers or social security numbers. Such techniques have the potential to identify drives of interest from a large set, provide additional information about events that occurred on a single disk, and potentially determine social network membership. Another analysis technique that has significantly advanced in recent years is the use of timelines. Tools currently exist that can extract dates and times from the file system metadata (i.e. MACE times) and also examine the content of certain file types and extract metadata from within. This approach provides a great deal of data that can assist with an investigation, but also compounds the problem of having too much data to examine. A recent paper adds an additional timeline analysis capability, by automatically producing a high-level summary of the activity on a computer system, by combining sets of low-level events into high-level events, for example reducing a setupapi event and several events from the Windows Registry to a single event of ‘a USB stick was connected’. This paper provides an investigation into the extent to which events in such a high-level timeline have the properties suitable to assist with Cross-Drive Analysis. The paper provides several examples that use timelines generated from multiple disk images, including USB stick connections, Skype calls, and access to files on a memory card.